Lycopene‐Based Bionic Membrane for Stable Perovskite Photovoltaics - Dong, Chong; Li, Xiao‐Mei; Ma, Chang; Yang, Wen‐Fan; Cao, Jun‐Jie; Igbari, Femi; Wang, Zhao‐Kui; Liao, Liang‐Sheng (Advanced functional materials, 2021)
Perovskite (PVSK) photovoltaics have been a promising field in the exploitation of renewable energy due to the fascinating performances of PVSK materials and devices. Although the efficiency is gradually approaching that of traditional solar cells, the stability is still a challenge. Hence, tomato lycopene, a botanic antioxidant, is introduced as a modification layer on the PVSK absorber layer to prevent moisture and oxygen erosion, for enhanced both intrinsic and environmental stabilities. This inserted protection layer can also interact with the PVSK material through carbon‐halogen bonds and influence its crystallinity. Therefore, PVSK films are obtained with less defects and better intrinsic stability. The device achieved a champion outdoor efficiency at AM 1.5G more than 21% and its indoor efficiency at 1000 lux can reach 40.24%. In addition, the efficiency can keep almost 90% of the original value after exposure to wet oxygen ambience for 1000 h. The antioxidant gives a unique perspective towards enhancing the stability of solar cells Lycopene, a botanic antioxidant, is introduced to modify the perovskite film for adjusting crystallization through carbon‐halogen bonds, and preventing moisture and oxygen erosion. Therefore, the optimized device yields efficiencies of 21.04% under 100 mW cm−2 and 40.24% at 1000 lux. It also retains almost 90% of the original efficiency value after exposure to wet oxygen ambience for 1000 h.